2008
DOI: 10.1097/brs.0b013e31817d8241
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Noninvasive Halo in Children

Abstract: A noninvasive halo was used successfully for postoperative immobilization of children with stable cervical spines. This device was particularly useful for the gentle and safe reduction of C1-C2 subluxations, and for postoperative immobilization in an overcorrected position following stenocleidomastoid release for congenital muscular torticollis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…Skaggs et al 22 have reported a very low complication rate in their study with pinless halos. In their cohort of 30 patients, only 1 patient developed a complication who had anterior migration of the fibular strut graft following cervical fusion without instrumentation; the fusion healed without further surgical intervention.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Skaggs et al 22 have reported a very low complication rate in their study with pinless halos. In their cohort of 30 patients, only 1 patient developed a complication who had anterior migration of the fibular strut graft following cervical fusion without instrumentation; the fusion healed without further surgical intervention.…”
Section: Discussionmentioning
confidence: 74%
“…22 In addition to these indications, we also used the pinless halo for stable occipital condyle fractures, which healed well with the pinless halo. In our cohort, no patients treated with a pinless halo had unstable fractures or unstable cervical fusions.…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly used in radiosurgery for the treatment of intracranial lesions this method may not be ideal for fractionated treatments over the course of multiple days. Other attractive options are the use of the Lerman non-invasive halo system [ 29 ] or the cervical-thoracic orthosis (CTO/Minerva brace) [ 30 , 31 ] in combination with the conventional head and shoulder mask for added reinforcement and better immobilization of the lower C-spine. The Lerman halo system has been developed as a non-invasive immobilization system in children.…”
Section: Discussionmentioning
confidence: 99%
“…Skaggs et al [4] berichten über gute Ergebnisse mit einem sog. noninvasiven Halo, letztlich einem erweiterten Orthesensystem, das den Kopf helmförmig, jedoch mit ausreichenden Freiräumen umfasst.…”
Section: Alternativenunclassified
“…Hierbei sind insbesondere Krankheitsbilder wie die Osteogenesis imperfecta, die fibröse Dysplasie und auch Kinder mit Hydrozephalus zu beachten. Bei diesen Konstellationen ist eine vorherige Abklärung mittels CT notwendig[4]. Arkader et al[8] führen eine solche CT-Abklärung bei allen Kindern unter 3 Jahren durch, um die Dicke der Schädelkalotte und die Suturen sicher beurteilen zu können.…”
unclassified